Advanced diabetic retinopathy detection with the R-CNN: A unified visual health solution - Sri Sravya, Valluri; Naga Srinivasu, Parvathaneni; Shafi, Jana; Hołubowski, Waldemar; Zielonka, Adam (Zielona Góra: Uniwersytet Zielonogórski)
Diabetic retinopathy (DR) can cause blindness and vision impairment. This degenerative eye condition may lead to an irreversible vision loss. The prevalence of vision impairment and blindness caused by DR emphasizes the critical need for better screening and therapy measures. DR aetiology involves persistent hyperglycemia-induced microvascular abnormalities, oxidative stress, inflammatory reactions, and retinal blood flow changes. Common screening methods for retinal issues include fundus photography, OCT, and fluorescein angiography. For those with diabetic macular edema (DME), it is a common cause of vision loss.
Keywords: disease diagnosis; diabetic retinopathy; convolutional neural networks